2016
DOI: 10.1155/2016/4709687
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electrical, Dielectric, and Magnetic Properties of Cd2+ Substituted Nickel Ferrite Nanoparticles

Abstract: In the present investigation structural, electric, magnetic, and frequency dependent dielectric properties of Ni1-xCdxFe2O4 ferrite nanoparticles (NPs) (where x=0.2, 0.4, 0.6, and 0.8) prepared by sol-gel autocombustion method were studied. The crystallite size (t) (46.89~58.40 nm) was estimated from X-ray diffraction data with the postconfirmation of single phase spinel structure. Spherical shaped, fused grain nature with intergranular diffusion in Ni1-xCdxFe2O4 NPs was observed in scanning electron micrograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 41 publications
2
6
1
Order By: Relevance
“…So, έ decreases as increases of the applied field. Same behavior was observed in many spinel ferrites [55,56]. Fig.…”
Section: Dielectric Propertiessupporting
confidence: 77%
See 1 more Smart Citation
“…So, έ decreases as increases of the applied field. Same behavior was observed in many spinel ferrites [55,56]. Fig.…”
Section: Dielectric Propertiessupporting
confidence: 77%
“…From Fig. 10 (a, b, & c) it is clearly shown that, έ decreases steeply at lower frequency and become nearly constant values for all samples at higher frequencies and increases with increasing temperature which are in agreement with spinel ferrites [55,56]. Same behavior can be obtained for ἕ as shown in Fig.…”
Section: Dielectric Propertiessupporting
confidence: 77%
“…For samples with x  0.3 the TC determined theoretically agrees very well with experimentally determined TC indicating the applicability of theoretical model to the present study. The experimental values TC are lower than that of reported by Devmunde et al [16] and are higher than that of reported by Lee et al [15]. The reduction of Curie temperature in the synthesized nanoparticles is attributed to the existence of a "dead" surface layer for each particle in which magnetic moments do not contribute to the magnetization in the applied field [17].…”
Section: Fig 5 -Variation Of Magnetic Permeability With Composition Xcontrasting
confidence: 54%
“…Though there are other absorption peaks, the dominants are the mentioned ones showing the ferrites' spinel structures. Moreover, in our case, the tetrahedral and octahedral site vibration could be inferred to the samples' constituent cations, i.e., Zn-O-Al-Cr and Ni-O vibrations, respectively [17].…”
Section: Ftir Analysismentioning
confidence: 56%